Documentation of fungal endophytes of black pepper (Piper nigrum L.) and their seed transmission studies - Sreeja, K; Anandaraj, M; Suseela Bhai, R (Journal of Spices and Aromatic Crops, 2020)
The present study envisaged to document the endophytic fungal association with black pepper through a series of in vitro and in planta investigations. Black pepper was found to harbour endophytic fungal flora belonging to the genera Alternaria, Acremonium, Aspergillus, Cladosporium, Chaetomium, Curvularia, Colletotrichum, Fusarium, Humicola, Paecilomyces, Rhizoctonia, Phoma and non-sporulating forms. Further, it was found that the endocarp of black pepper seed is free from culturable endophytic fungi. This was evident from the absence of culturable fungi in in vitro grown black pepper seedlings. The growth of fungi from the seedlings grown under green house conditions reveal that the fungal endophytes establish from fungal propagules falling on the (test) plants that may enter the plant tissues as back ground inoculum and grow as endophyte. This was also supported by the study that the type of endophytic fungi that harbour black pepper plants varied with geographical locations from where the samples were collected.